Evaluasi Program Dana Desa dalam Peningkatan Kesejahteraan Masyarakat di Desa Lebeteng Kec. Tarub Kab. Tegal - Koriyawati Koriyawati; Nihayatus Sholicah; Widyawati Widyawati; Dendy Patrija W (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to evaluate the effectiveness of the Village Fund program (Dana Desa) in enhancing community welfare in Lebeteng Village, Tarub district, Tegal Regency. Employing a qualitative approach, the research explores the implementation process, supporting factors, constraints, and its impact on local development comprehensively. Data were collected through in-depth interviews, field observations, and document analysis involving various stakeholders such as the village head, village apparatus, community members, and local leaders. The findings reveal that the Village Fund positively influences infrastructure development, access to basic services, local economic growth, and community empowerment. Active participation of residents in planning, implementation, and monitoring significantly boosts accountability and program sustainability. Cross-sector collaboration also plays a crucial role in expanding resource mobilization, accelerating target achievement, and strengthening synergy among actors involved. Nonetheless, challenges remain, including limited human resource capacity, transparency and accountability issues, and restricted access to technology and information. Therefore, efforts to enhance village officials' capacity, strengthen oversight mechanisms, and promote broader community participation are necessary to maximize and sustain the benefits of the Village Fund. The study concludes that the Village Fund has substantial potential as an effective development instrument when managed transparently, accountably, and inclusively. Successful implementation not only improves community socio-economic well-being but also fosters village independence and competitiveness, progressing toward a more developed, autonomous, and prosperous village. Overall, this program underscores the importance of participatory, transparent, and accountable governance in local development and highlights its role in realizing sustainable community progress, contributing to national policy refinement and village-level empowerment.